The Politics of Chinese Land: Partial Reform, Vested Interests, and Small Property - Qiao, Shitong (Columbia Journal of Asian Law, 2015)
This paper investigates the evolution of the Chinese land regime in the past three decades and focus on one question: why has the land use reform succeeded in the urban area, but not in the rural area? Through asking this question, it presents a holistic view of Chinese land reform, rather than the conventional “rural land rights conflict” picture. This paper argues that the so-called rural land problem is the consequence of China’s partial land use reform. In 1988, the Chinese government chose to conduct land use reform sequentially: first urban and then rural. It was a pragmatic move because it would provoke much less resistance. It also made local governments in China the biggest beneficiary and supporter of the partial reform. However, a beneficiary of partial reform does not necessarily support further reform because of the excessive rents available between the market of urban real estate and the government-controlled system of rural land development and transfer. On the other hand, Chinese farmers and other relevant groups have no voice or power in the political process of the reform, which makes it difficult for the central government to achieve an agenda that balances the interests of all relevant parties. Nevertheless, Chinese farmers have challenged the existing system by forming a huge small-property market to claim their interests in rural land, which counteracts the goals of the central and local governments and has led to adaptive policy changes. This case study of Chinese land reform provides a richer account of the political process of evolution of property rights.